Kidfluencer: Child Exploitation In Digital Space In Terms Of Child Protection Law - Fatmawati, Fahira; Lewoleba, Kayus Kayowuan (Dinasti Research, 2024)
Kidfluencer from the words Kid and Influencer is the term used for children who are used as content on social media by their parents and get ad-sense or endorsements from various well-known brands that pay high prices. However, if this phenomenon is seen from a legal perspective, it has violated the child protection law which can be called economic exploitation of children, because it is the same as utilizing children’s labor for profit. The purpose of this study is to determine the factor that cause kidfluencer and the form of legal protection for victims of exploitation in the form of kidfluencer. This research uses a normative juridical method with a statutory approach. The results explain that the most contributing factor in the emergence of kidfluencers is the family factor, because their parents are influencers or artists so their children are included in it. Furthermore, Indonesia does not yet have a regulation specifically governing kidfluencers, causing uncertainty regarding whether kidfluencers are part of child exploitation in social media and which institutions are obliged to protect kidfluencers.